15-4X=-X

Simple and best practice solution for 15-4X=-X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15-4X=-X equation:


Simplifying
15 + -4X = -1X

Solving
15 + -4X = -1X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add 'X' to each side of the equation.
15 + -4X + X = -1X + X

Combine like terms: -4X + X = -3X
15 + -3X = -1X + X

Combine like terms: -1X + X = 0
15 + -3X = 0

Add '-15' to each side of the equation.
15 + -15 + -3X = 0 + -15

Combine like terms: 15 + -15 = 0
0 + -3X = 0 + -15
-3X = 0 + -15

Combine like terms: 0 + -15 = -15
-3X = -15

Divide each side by '-3'.
X = 5

Simplifying
X = 5

See similar equations:

| 3(x-3)+5=4(x-2)-10 | | 5ab-6ab+a= | | 2senx-cosx=-4 | | P=20+6ln(2q+1) | | 13x+15=3x+215 | | B+280= | | I=IR | | 5x+5x+130=180 | | -12+5m+10m=-2m-10-m | | 4(3x+3)=14x+11-2x+1 | | (3a-5)(2a+3)=0 | | -8=x/4+3 | | 3y=5x-y | | 5x+10=-48-7x | | 5(-3x-7)=-4(4x+9) | | 6(x-1)-5=4x+2(-3+x) | | 55-(2c+3)=4c(c+6)+c | | 7y+9=30 | | 7x-5=5(x+11)+2x-10 | | -2(m+2)=-8 | | (4x^8+11x^6-7x^2+3)-(9x^8-5x^4+8x^2-4)=0 | | 0.009(x+200)+0.06x=63 | | f(x)=10xfor | | 9c-6c=-8+11 | | 5x+6x-40=100-9x | | 45-4x*5=80 | | 8x+48=9x | | 0.5x+0.7x=1.7 | | -8=3-2(c-4)+3 | | 8+20x=x-4 | | P=50h+200 | | 100x=1000findx |

Equations solver categories